Epistimologi Tadabur dalam Al Quran - Lailatul Mas'udah (MIYAH : Jurnal Studi Islam, 2019)
Abstrak: Every human being is given by God the gift of mind, mind and heart whose ability is able to be maximized in contemplating the signs of the greatness of God, both in the form of verses kauniyah or in the form of verses qauliyah. One method of contemplating the verses of the Qur'an is to take a taboo. With bertadabbur someone is expected to be able to get the wisdom and guidance contained in the verses of the Koran so that it can be a light in running life. In this study, trying to dismantle the meaning of tadabbur itself and various things related to tadabbur, such as the benefits of tadabbur, various types of tadabbur and some terms whose meanings are close to tadabbur. Using the literature study research method, the literature used in this study are several books and books, especially the commentary book as its primary source. There are several different functions and meanings contained in terms that are close to the word tadabbur, tafakkur is a person's activity in contemplating something related to natural events and as well as comparing with the verses of the Koran and relating to the cause and effect of a thing and torture. The tasyakkur is an activity in contemplating the goodness and grace that God has given to the servant.Keyword: Tadabbur, epistimologi, tafakkur